Community Schools in The National Context: The Social and Cultural Impact of Educational Reform Movements on American Rural Schools - Alan J. DeYoung; Paul Theobald (Journal of Research in Rural Education, 1991)
This paper discusses how historical influences have transformed community schools, both rural and urban, through the decades.. The s~cial an~ cultural impacts of educational reform movements and how they ha~e affected rural schools I~ exammed, With emphasis being placed on the importance of understanding the venous roles a school holds in a rural community.